Dietary adequacies and anthropometric measurements in children with poor appetite according to their mothers - Bozbulut, Rukiye; Çuhacı Çakır, Bahar; Yassıbaş, Emine; Duyan Çamurdan, Aysu (The Turkish Journal of Pediatrics, 2025)
Background. This cross-sectional study aimed to evaluate the dietary adequacy and growth patterns of children considered to have a poor appetite by their mothers and to compare these findings with established reference values.Methods. A total of 200 volunteer mothers who applied because they thought their children (2-9 years) had poor appetites participated in the study. Maternal reports were obtained through a comprehensive questionnaire, encompassing socio-demographic characteristics, dietary habits, the Children’s Eating Behavior Questionnaire (CEBQ), anthropometric measurements, and three-day food consumption records. Children’s anthropometric measurements were evaluated according to z-scores based on the World Health Organization standards, and daily energy and nutrient intake amounts were determined from food consumption records. Dietary adequacy was calculated according to dietary reference intakes (DRI).Results. It was found that 90.5% of the children had normal height, and 6.0% were stunted/severely stunted. According to body mass index (BMI)-for-age z-scores (BAZ), 92.5% of the children had normal weight. All mothers perceived that their children had poor appetite, and 55% also believed their children to be underweight, whereas objective measurements indicated that 90% of these children had normal weight. The scores of sub-dimensions of “Food Responsiveness” and “Emotional Overeating” of CEBQ for girls (12.6±2.7 and 9.6±2.3, respectively) were significantly higher than those for boys (11.2±2.8 and 8.7±2.4, respectively) (p
Keywords: eating behaviors; body mass index; appetite; dietary adequacy